Randomized trial of emtricitabine/tenofovir disoproxil fumarate after hepatitis B immunoglobulin withdrawal after liver transplantation. Issue 6 (9th April 2013) - Teperman, Lewis W.; Poordad, Fred; Bzowej, Natalie; Martin, Paul; Pungpapong, Surakit; Schiano, Thomas; Flaherty, John; Dinh, Phillip; Rossi, Stephen; Subramanian, G. Mani; Spivey, James
<x xml:space="preserve">Abstract</x> Long‐term prophylaxis with hepatitis B immunoglobulin (HBIG) for the prevention of hepatitis B virus (HBV) recurrence after orthotopic liver transplantation (OLT) in patients with chronic HBV infection is inconvenient and costly. This randomized, prospective phase 2 study compared emtricitabine (FTC)/tenofovir disoproxil fumarate (TDF) after HBIG withdrawal to FTC/TDF plus HBIG for the prevention of HBV recurrence after OLT. Forty patients with a median time since liver transplantation of 3.4 years (interquartile range = 1.9‐5.6 years) received 24 weeks of open‐label FTC/TDF plus HBIG before randomization. Patients who maintained confirmed viral suppression were randomized to continue FTC/TDF plus HBIG (n = 19) or receive FTC/TDF alone (n = 18) for an additional 72 weeks. No patient experienced HBV recurrence through 72 weeks of the study while he or she was receiving the randomized treatment. Both treatment arms were safe and well tolerated; no serious or severe drug‐related adverse events were observed. Renal function was consistent with that observed in a posttransplant population. The withdrawal of HBIG after 6 months' treatment with FTC/TDF should be considered in liver transplant recipients to prevent chronic HBV recurrence. Liver Transpl 19:594–601, 2013. © 2013 AASLD.